Neglected Tropical Diseases in the Post-Genomic Era - Buscaglia, Carlos Andres (2015)
Neglected tropical diseases (NTDs) are a group of viral, bacterial, and eukaryotic parasitic diseases that are especially endemic in low-income populations, with a large health and economic impact on both the developing and developed world. The structure and dynamics of the genomes of the organisms causing these diseases, as well as the modes of expression, exchange, and transmission of their genetic information, often deviate from those found in classical, model organism-centric textbooks. We assess the role of basic and applied genetic research in our understanding of key aspects of their biology and evolution, and discuss the impact of novel high-throughput approaches spawned by the post-genomic era on the development of next-generation drugs, vaccines, molecular epidemiology, and/or diagnostic tools for these important pathogens.